The Influence of Customer Relationship Management and Service Quality on Customer Satisfaction On the Tokopedia Marketplace - Puti Lenggo Ginny; Rinintha Parameswari; Canggih Gumanky Farunik (EMaBi: Ekonomi Dan Manajemen Bisnis, 2022)
Tokopedia is a huge marketplace in Indonesia, such a state becomes one of the reasons of which the study was conducted, namely to discover the extent to which Customer Relationship Management (X1) and Service Quality (X2) affect Customer Satisfaction (Y). This study was a casual descriptive research that collected data through questionnaire as primary data. The study acquired 50 respondents in which the results were processed using SPSS26 to discover the effect of Variables X1 and X2 on Y. The study results have concluded that the factors of customer relationship management and service quality positively affect the decision making of customers. These two factors affected more than 64 percent in establishing the condition of customer satisfaction.